2022
DOI: 10.1371/journal.pone.0266081
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, attitudes and acceptability of the HPV vaccine among female university students in Morocco

Abstract: Background In Morocco, cervical cancer is the second most common cancer affecting women behind breast cancer. The Human PapillomaVirus (HPV) vaccine has been available in Morocco since 2008 but its introduction in the national immunization program is still under discussion. There is limited data regarding acceptability and predictors of HPV vaccine acceptability among Moroccan young women. This study aimed to evaluate the awareness of female university students of HPV and the vaccine and to identify predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…More than two-thirds 68.9% with 95% CI [64.2%-73.8%] of responders were willing to take the HPV vaccine. This study finding was in line with a previous study conducted in mainland China 18 and Morocco, 19 revealed that 67.3% and 67% of adolescents were willing to receive the HPV vaccine. However, the results are relatively lower than those of studies conducted in Italy, 20 India, 21 Fujian province, China, 22 Texas; USA, 23 and Mali 24 revealed that 81.7%, 92.5%, 80%,77%, and 80% of females students were willing to get vaccinated.…”
Section: Discussionsupporting
confidence: 92%
“…More than two-thirds 68.9% with 95% CI [64.2%-73.8%] of responders were willing to take the HPV vaccine. This study finding was in line with a previous study conducted in mainland China 18 and Morocco, 19 revealed that 67.3% and 67% of adolescents were willing to receive the HPV vaccine. However, the results are relatively lower than those of studies conducted in Italy, 20 India, 21 Fujian province, China, 22 Texas; USA, 23 and Mali 24 revealed that 81.7%, 92.5%, 80%,77%, and 80% of females students were willing to get vaccinated.…”
Section: Discussionsupporting
confidence: 92%
“…66.7% of the participants in our study intended to get vaccinated compared to 48.9% of people in Saudi Arabia [ 25 ]. Our study results are similar to the other studies reporting lack of awareness as the leading reason to refuse HPV vaccination [ 26 - 29 ]. We also found a significant association between younger age and health care setting as factors with higher acceptability to get HPV vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…This allowed a better reflection on the dispersion of awareness and attitudes on HPV and its vaccination, and perception on self-sampling to screen for HPV and cervical cancer. Similar to the implications of this study, a study in Morocco found that non-health related students were less willing than health-related students to get vaccinated [ 12 ].…”
Section: Discussionsupporting
confidence: 77%